The benefit of time-of-flight in PET imaging: Experimental and clinical results - Karp, Joel S. (2008)
Significant improvements have made it possible to add the technology of time-of-flight (TOF) to improve PET imaging, particularly for oncology applications. The goals of this work were to investigate the benefits of TOF in experimental phantoms and to determine how these benefits translate into improved performance for patient imaging. METHODS: The Gemini TF scanner (Philips Medical Systems) used in this study is a fully 3D scanner and utilizes the scintillator LYSO with a system timing resolution of ~600 ps. The data are acquired in list-mode and reconstructed with an ML-EM algorithm; the system model includes the TOF kernel and corrections for attenuation, detector normalization, randoms, and scatter. The scatter correction is an extension of the modelbased single-scatter simulation to include the time domain. Phantom measurements to study the benefit of TOF include 27-cm and 35-cm diameter distributions with spheres ranging in size from 10 mm to 37 mm. To assess the benefit of TOF PET for clinical imaging, patient studies are quantitatively analyzed. RESULTS: The lesion phantom studies demonstrate the improved contrast of the smallest spheres with TOF compared to non-TOF and also confirm the faster convergence of contrast with TOF. These gains are evident from visual inspection of the images, as well as a quantitative evaluation of contrast recovery of the spheres and noise in the background. The gains with TOF are higher for larger objects. These results correlate with patient studies in which lesions are seen more clearly and with higher uptake at comparable noise for TOF than with non-TOF. CONCLUSION: TOF leads to a better contrast vs. noise trade-off than non-TOF but one that is difficult to quantify in terms of a simple sensitivity gain improvement: a single gain factor for TOF improvement does not include the increased rate of convergence with TOF, nor does it consider that TOF may converge to a different contrast than non-TOF. The experimental phantoms results agree with those of prior simulations and help explain the improved image quality with TOF for patient oncology studies.